The dependence of dynamic phase transitions on parameters - Piechór, K. (Archives of Mechanics, 1998)
We consider phase changes described by a second order ordinary differential equation. The equation depends parametrically on the states of rest and the speed of the wave. We prove that, under some additional conditions, the solution is differentiable with respect to any of these parameters. As an application of the general theory we discuss the case when the data are close to the Maxwell line and obtain results generalising those of the previous authors.